Food Wastage, a Threat to Indonesian Tourism: Pemborosan Makanan, Ancaman bagi Pariwisata Indonesia - Lemy, Diena Mutiara; Kusumo, Elang; Brian, Reagan (Politeknik Pariwisata Makassar, Indonesia, 2024)
The tourism sector have the impact to environmental as it shifts towards sustainable tourism development. Food waste is a one of environment continuing global issue possessing sustainability challenges in the tourism sector. Food waste is edible food that is discarded, negatively impacting environmental health. As per the 2020 report from the Food and Agriculture Organization (FAO), approximately one-third of all food produced for human consumption globally is wasted or discarded. Indonesia is among the leading producers of food waste in Southeast Asia. The 2021 UNEP annual report, food waste in Indonesia totals 20.93 million tons. The Tourism food and beverage sector, some of the biggest contributors to food waste, along with, is also by the behavior of people who may not be aware of the negative effects on food waste. This study using Qualitative method approach, with the data such as media journals, reports, journals articles and books, and will explore the behavior of domestic tourists towards food waste, especially in the Labuan Bajo area, which is one of the super priority tourist destinations in Indonesia. The study's findings give an overview of how people's attitudes and knowledge are influenced food wastage behavior.